2006
DOI: 10.1021/ja058550q
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of β-Aryl Eliminations from Rh(I) Alkoxides

Abstract: beta-Aryl eliminations from a series of rhodium(I) alkoxides to form rhodium aryl complexes and free ketones are reported. Tertiary phenylmethoxide complexes [Rh(PEt3)n(OCPhRR')] (n = 2, 3) were prepared via alcoholysis of {Rh(PEt3)2[N(SiMe3)2} by the corresponding alcohols HOCPhRR' in the presence and absence of added PEt3. Heating of these complexes in the presence of added PEt3 generated the rhodium phenyl complex, (PEt3)3RhPh, and the corresponding ketones in good to high yields. Kinetic results are most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(59 citation statements)
references
References 20 publications
(24 reference statements)
3
55
0
Order By: Relevance
“…Cramer et al suggested that the reaction may be initiated by formation of rhodium alkoxide species 3 (Scheme 2), [13] the CÀC bond breaking of the cyclobutane group then occurs by b-C elimination. [14] The resulting intermediate 4 then undergoes 1,4-Rh transfer [15,16] to give intermediate 5. Thereafter, the carbonyl C=O bond inserts into the RhÀC(aryl) bond to give intermediate 6, from which the release of product and the regeneration of rhodium catalyst can finally occur.…”
Section: Introductionmentioning
confidence: 99%
“…Cramer et al suggested that the reaction may be initiated by formation of rhodium alkoxide species 3 (Scheme 2), [13] the CÀC bond breaking of the cyclobutane group then occurs by b-C elimination. [14] The resulting intermediate 4 then undergoes 1,4-Rh transfer [15,16] to give intermediate 5. Thereafter, the carbonyl C=O bond inserts into the RhÀC(aryl) bond to give intermediate 6, from which the release of product and the regeneration of rhodium catalyst can finally occur.…”
Section: Introductionmentioning
confidence: 99%
“…2b, bottom). The hydroxy group of (±)-5a is exchanged onto the rhodium hydroxide to generate rhodium benzocyclobutenolate Ca, in which the benzene ring likely p-coordinates to rhodium 49 . Next follows b-carbon elimination, for which the p-coordination facilitates site-selective cleavage of the C(ipso)-C(sp 3 ) bond to furnish arylrhodium Da.…”
Section: Resultsmentioning
confidence: 99%
“…Then complex 4 may undergo an intramolecular S N Ar process to afford the complex 5 upon heating to 160 °C,13 thereby generating the Rh III complex 6 (an alternative process through 1,4‐elimination of Ar–Rh– t OBu from 4 with subsequent conjugate addition of Ar–Rh– t OBu to the resulting enone species may be excluded based on the result of the cross‐experiment), which could release one molecule of acetone (detected by GC‐MS) to afford the Rh III /Me complex 7 14. Finally, reaction of the previously formed t BuOH with complex 7 can release one molecule of the desired product 2 and form [Rh III (Me)( t OBu)] ( 8 ),14e,f, 15 which could regenerate the Rh I catalyst through a reductive elimination process by releasing t BuOMe (detected by GC‐MS).…”
Section: Methodsmentioning
confidence: 99%